Cozinha caipira e construção da paulistanidade - Rosa, Lucas Souza (2021)
Based on the assumption that cooking is one of the elements of which culture is made, and that cuisine is linked to the field of identity construction, this study questions the daily food routine in the city of São Paulo in the early twentieth century to assess how the process of formulating and constructing the São Paulo way of living came about from the standpoint of food. This research focuses on a range of documentation, including memorials, minutes and historical records of the São Paulo City Council, press releases, and manuals of conduct, among others. Firstly, this paper identifies the “caipira” (country) cuisine, its emergence and characteristics, to understand which elements of “caipira” culture apparently helped create habits, consumption habits, customs, food practices and rural supply in the urban routine of São Paulo. The analysis focuses on food spaces in homes and places that sold food (hotels, restaurants, cafes, and bakeries), focusing on sociability issues and highlighting the kitchen as a privileged site of food production. It discusses how, in everyday life, the kitchen preserved firmly established practices and customs while the environment underwent transformations resulting from new notions regarding hygiene and public health. The research further discusses foreign influences on culinary practices, discussing the polemics regarding foreignness and regionalism, which places the “caipira” cuisine as a reference in constructing the São Paulo identity. Thus, it seeks to understand how what has been idealized as "caipira" roots formed a matrix that coexists in a process of appropriations, exclusions, and redefinitions of culinary practices in the so-called “caipira metropolis”